Transient reduction in dendritic spine density in brain-specific profilin1 mutant mice is associated with behavioral deficits - Sungur, A. Özge; Zeitouny, Caroline; Gabele, Lea; Metz, Isabell; Wöhr, Markus; Michaelsen-Preusse, Kristin; Rust, Marco B. (Frontiers in Molecular Neuroscience, 2022)
Actin filaments form the backbone of dendritic spines, the postsynaptic compartment of most excitatory synapses in the brain. Spine density changes affect brain function, and postsynaptic actin defects have been implicated in various neuropathies. It is mandatory to identify the actin regulators that control spine density. Based on previous studies, we hypothesized a role for the actin regulator profilin1 in spine formation. We report reduced hippocampal spine density in juvenile profilin1 mutant mice together with impairments in memory formation and reduced ultrasonic communication during active social behavior. Our results therefore underline a previously suggested function of profilin1 in controlling spine formation and behavior in juvenile mice.